Paediatric new onset type 1 diabetes and diabetic ketoacidosis during the COVID-19 pandemic in Malaysia - Yee, Lin Lee; Wan Ahmad Nasir, Fatin Farihah; Selveindran, Nalini M; Anuar Zaini, Azriyanti; Poi, Giok Lim; Jalaludin, Muhammad Yazid (Elsevier Ireland, 2023)
Aims: Despite emerging evidence of increased paediatric diabetes mellitus (DM) and diabetic ketoacidosis (DKA) worldwide following the COVID-19 pandemic, studies in Asia are lacking. We aimed to determine the frequency, demographics, and clinical characteristics of new onset type 1 DM (T1DM) during the pandemic in Malaysia. Methods: This is a retrospective multicenter study involving new onset T1DM paediatric patients in Klang Valley, Malaysia during two time periods ie 18th September 2017-17th March 2020 (pre-pandemic) and 18th March 2020-17th September 2022 (pandemic). Results: There was a total of 180 patients with new onset T1DM during the 5-year study period (71 pre-pandemic, 109 pandemic). An increase in frequency of T1DM was observed during the pandemic (52 in 2021, 38 in 2020, 27 in 2019 and 30 in 2018). A significantly greater proportion of patients presented with DKA (79.8 vs 64.8), especially severe DKA (46.8 vs 28.2) during the pandemic. Serum glucose was significantly higher (28.2 mmol vs 25.9 mmol/L) with lower venous pH (7.10 vs 7.16), but HbA1c was unchanged. Conclusions: New onset T1DM increased during the pandemic, with a greater proportion having severe DKA. Further studies are required to evaluate the mechanism leading to this rise to guide intervention measures.